Farewell to the Factory: Auto Workers in the Late Twentieth Century - Yanarella, Ernest J. (Labour / Le Travail, 1998)
The article reviews the book, "Farewell to the Factory: Auto Workers in the Late Twentieth Century," by Ruth Milkman.